Jamaica : Interim Staff Report Under Intensified Surveillance. (IMF Staff Country Reports; Country Report, 2006)
The Jamaican economy made progress in reducing public debt despite adverse shocks and revenue shortfalls through fiscal consolidation under intensified IMF surveillance. IMF staff monitors the implementation of economic strategy formulated by the authorities. Executive Directors welcomed the monetary stance and the strategy to widen the tax base and strengthen the underlying fiscal position by improving tax administration. They advised to strengthen fiscal consolidation, accelerate structural reforms, and strengthen the resilience of the financial system. They emphasized the need for intensified fiscal efforts to reduce debt rapidly.